Pengaruh Pembelajaran di Perguruan Tinggi, Pengetahuan Keuangan, Kontrol Perilaku, Pendapatan Orang Tua, dan Personal Income terhadap Financial Behavior Mahasiswa di Surabaya - Dita Kurnia Rahmadani; Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study examines students' financial behaviour from the economics faculty at a private university in Surabaya and analyses the relationship between college learning, financial knowledge, behaviour control, parents' income, and personal income. The object of this research is the student in Surabaya and data collection techniques using purposive sampling. The total number of respondents obtained is 278 by distributing online questionnaires. This research is conclusive causality and uses Structural Equation Modeling (SEM) analysis technique in AMOS software version 24. This study showed that college learning, financial knowledge, behaviour control, parents' income, and personal income significantly affect financial behaviour. It proves that knowledge of money affects considering financial expenditures, and reasonable behavioural control can control buying behaviour, and the more income increases, the more financial expenses will increase. This study can be a valuable reference for various parties, mainly students, who must begin to learn to organise and make decisions in managing their finances. A person's sense of responsibility in their financial behaviour will help them make good money decisions by budgeting, saving, controlling spending, investing, and paying debts on time.